Aircraft conceptual design decision through operational modelling - Harasani, W. (Cranfield University, 2005)
Aircraft manufacturing is not only a difficult business but also a very competitive one, the consequences of any drop in sales would cost billions, loss of jobs, and maybe an economical failure. Therefore, concentrating on just flight performance and adding new technologies just because they exit is not enough to win the airlines attention, especially the flow cost carriers. Manufactures must be able to convince operators that the application of a new design or technology will produce a favourable change in the bottom line of their balance sheets and not just a reduction in fuel burn. Aircraft designers must put more emphasis on what happens to the aircraft after it leaves the assembly line, through the designed life operation cycle of the aircraft with the airline customer, quality should be built in to the aircraft. Knowing what are the airline's concerns, how the aircraft with a given design behaves, and the issues that the airline has, is vital. Firstly, it is important to know what are the issues that the airline has, the costumer (airlines) needs are identified, and, since fleet planning is the top level decision making department in the airline in which a decision is made to buy one aircraft over the other, it is important to understand the process and the elements that are involved in fleet planning. So fleet planning was studied. Second different technologies for the design have been looked at and selected. Then the aircraft, airline, airport, and air traffic control are studied, as well as the interaction between them. A key element of the research is a simulation program DEBOS that has been built to see the impact of the different design technologies and concepts through the operation of a simulation fleet size of 23 aircraft. The Boeing777 aircraft has been chosen to be the base line of the study. Finally, it was found that a given technology with improved performance, or a new concept, would improve the aircraft attractiveness only if it has better life cycle behaviour characteristics.